Characteristics of Patients with Newly Diagnosed Multiple Sclerosis – A 5-year Study at Benghazi Medical Center, Benghazi, Libya - Magda Elshukri; Kathloum Elkaseh; Anwaar Mukhtar Bennour; Heba Abdelrazek El-Zawawi (APIK Journal of Internal Medicine)
Background: Epidemiology of multiple sclerosis (MS) in Libya had been studied at different intervals, but not focused on newly diagnosed patients with MS (pwMS). Objective: The objective of this study was to study the demographic, clinical, and paraclinical characteristics of pwMS and to find out whether the Libyan population had similar features of MS compared to other Arab countries and the rest of the world. Materials and Methods: This was a retrospective study conducted at MS clinic in Benghazi Medical Centre, Libya, from November 1, 2016 to December 31, 2021. The patients who were fulfilling the 2017 McDonald’s diagnostic criteria and registered at the MS clinic were included in the study. Data were collected and statistically analyzed with appropriate statistical tools. Results: The study included 102 patients, 69 (68%) were females. The mean age of participants was 28 ± 10 and 30 ± 9 years, at symptom and diagnosis onset, respectively. The most common symptoms were motor (n = 63, 62%). Relapsing-remitting course was reported in 96 (94%). Eighty-four patients (82%) had a low disability score (1.5 ± 1.6). Magnetic resonance imaging (MRI) images showed hyperintense white matter lesions, supratentorial (n = 102, 100%), infratentorial (n = 20, 20%), and spinal cord (n = 47, 46%). Half of the patients (50%) underwent MRI with gadolinium, and only four patients showed an enhancing lesion. Visual evoked potential was performed in 61/102 (60%), of whom 37/61 (60%) had optic neuritis. All patients (n = 102, 100%) received treatment with interferon β. The mean value for Vitamin D was 17.25 ± 12.37 ng/ml. Conclusion: Newly diagnosed pwMS in the eastern part of Libya is characterized by a mild disability as manifested by a low disability score. Other features are comparable to results from neighboring Arab countries and the rest of the world. Research on regional MS should be improved and facilitated through the establishment of a Libyan MS registry, which will explore data about disease severity and/or progression and the response to treatment.